Intentional human poisoning by long-acting anticoagulant rodenticide - Mechan-Méndez, Víctor (2021)
A 19-year-old male, who for suicidal purposes ingested clonazepam tablets and 250 pellets of a rodenticide containing 2.5 mg of brodifacoum. He received general care and in the following days he presented bleeding and prolonged prothrombin time (PT). It was treated with intravenous phytonadioneand fresh plasma, noting that urinary cumarin metabolites disappeared after two months and that PT was normalized after nine months.